ANALISIS PENCEGAHAN DAN PENANGANAN KEKERASAN (TPPK) DALAM PENCEGAHAN BULLYING BERBASIS NILAI-NILAI ISLAM (STUDI KASUS DI SMKN 22 JAKARTA) - Muhammad Virliadli Azzuhri; Raihan; Nahuda Alwi; Choiruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to look at how the Violence Prevention and Handling Team (TPPK) works in preventing bullying based on Islamic values at SMKN 22 Jakarta. The research came about because verbal bullying is still happening, like teasing, giving inappropriate nicknames, over-the-top jokes, insults about physical conditions, and put-down comments toward friends. Verbal bullying is influenced by the idea that teasing is just a joke, peer pressure, lack of empathy, low emotional control, and not really understanding Islamic values, especially about keeping your words in check. The study uses a qualitative approach with a case study method. Data was collected through observations, interviews, and documentation. The informants include student representatives, guidance and counseling teachers, Islamic education teachers, and TPPK members. Data validity was checked through source triangulation and technique triangulation, Meanwhile, the data analysis used the Miles, Huberman, and Saldaña model. The research results show that TPPK has carried out the functions of preventing and handling bullying through socialization, counseling services, character building, mentoring, mediation, coordination with teachers and parents, as well as monitoring students. TPPK also integrates Islamic values, such as controlling speech, brotherhood, compassion, tolerance, empathy, responsibility, and noble character. The application of these values increases respect for each other, care, polite communication, courage to report bullying, and reduces verbal bullying cases. This study concludes that TPPK plays an important role in creating a safe, comfortable, conducive school environment and supports sustainable bullying prevention through collaboration with teachers, parents, students, and the strengthening of Islamic values.